Cognitive performance in a retired NFL population: Does position played and racial identity impact cognition? - Diah, K. C. (Nova Southeastern University, 2020)
Cognitive functioning is integral to everyday life as it involves mental processes crucial to everyday survival. Over the last decade, there has been increasing focus and controversy surrounding concussions sustained by players in popular contact sports. This attention has sparked national debates that continue to polarize both the sports and scientific communities on the long-standing neuroanatomical, cognitive, and psychiatric challenges that many retired NFL players experience later in life (Alosco et al., 2017; Hart et al., 2013). While studies have been conducted on the predictors of long-term neuropsychiatric and psychosocial outcomes following a traumatic brain injury, there are few studies that have explored the factors that affect long-term effects of playing football through using a comprehensive neuropsychological battery. As emerging studies continue to shed light on the association between concussions and the neurological changes of the brain that lead to behavioral, mood and cognitive deficits of individuals who participate in these sports, it is imperative to understand factors that could mitigate these effects in order to inform policy at all levels of play. Thus, the current study examined the impact of player position and racial identity as predictors of cognitive performance among retired NFL players and found that retired athletes who identified as Black had lower cognitive performance when compared to White athletes. Furthermore, position played while in the NFL did not independently account for differences in cognitive performance but accounted for sociodemographic differences within this population. Racial identity and player position revealed unique interaction effects that indicate the need to study these variables further. Taken together, this study highlights the need for continued involvement of Black participants in traumatic brain injury and chronic traumatic encephalopathy related research.